Triplet Exciton Enhanced Radioluminescence of Ga3+/Tb3+ Metallacrown Scintillators for X‐Ray Detection. Issue 3 (25th November 2021) - Chen, Zi; Lu, Dongdong; Xie, Hangqing; Yang, Xiaolei; Li, Yang; Bao, Chenhao; Lei, Lei; Xu, Shiqing
Abstract: The increasing demand for radiation detection in many applications has led to demanding requirements for scintillators. Realizing low‐dose, pollution‐free, and reliable X‐ray detection has become a key technical challenge. Here, a triplet‐enhanced lanthanide radioluminescence (RL) material Ga 3+ /Tb 3+ metallacrowns (Tb‐1) is reported. This Tb‐1 crystal emits bright green luminescence under ultraviolet light or X‐ray excitation, and the emission intensity is 286 and 242 times that of Tb 3+ in inorganic salt, respectively. Tb‐1 crystal is further passivated by trioctylphosphine oxide (TOPO), and the enhanced RL intensity is equivalent to that of commercial Tl‐doped cesium iodide scintillator. In addition, RL of Tb‐1–TOPO has an extremely narrow full width at half maximum and an excellent linear response to the X‐ray dose rate. The detection limit is calculated to be 0.146 μGy s −1, which is 38 times lower than typical medical imaging doses. Triplet‐enhanced lanthanide RL provides new ideas for replacing scintillators that require high temperature synthesis processes such as inorganic phosphors and ceramics, and provides a new alternative scintillator material for flexible X‐ray monitoring, bioimaging, radiotherapy, and other applications. Abstract : The mechanism of triplet‐exciton‐enhanced radioluminescence (RL) of a Ga 3+ /Tb 3+ metallacrown complex material (Tb‐1) is studied. After secondary electron, thermalization, intersystem crossing, and triplet energy transfer, the final radiation recombination center of the material is Tb 3+ . Moreover, the RL of Tb‐1 is further enhanced by surface passivation, and the X‐ray detection limit of the passivated Tb‐1 is 0.146 μGy s −1 .